STUDI PERILAKU DAN KESIAPAN PROFESIONAL DI JAKARTA DALAM MENGADOPSI TEKNOLOGI GENERATIVE AI: STUDY OF BEHAVIOR AND PROFESSIONAL READINESS IN JAKARTA IN ADOPTING TECHNOLOGY GENERATIVE AI - Jefri Yushendri; Danang Rizki Ginanjar; Asti Nurafala Sahir (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid development of Artificial Intelligence (AI), particularly Generative AI, has driven significant transformation across various sectors of society and the global economy. However, at the local level, particularly in DKI Jakarta as the center of national economic activity, there remains a gap between the potential utilization of AI and the readiness to adopt it. This study aims to analyze the behavior and readiness of AI users in Jakarta by comparing the public and private sectors. Data were collected through an online survey of professionals in Jakarta with a total of 805 respondents and analyzed using a quantitative approach, supported by non-hierarchical classification techniques (K-Means Clustering). The results show that the largest group of AI users falls into the Explorer category (51%), followed by the Skeptic category (25%), indicating a high level of interest in AI that is not yet matched by adequate technical readiness. The public sector demonstrates a more innovative and adaptive adoption pattern, while the private sector tends to be more cautious and efficiency-oriented. The findings of this study are expected to serve as a basis for formulating contextual and data-driven digital transformation policies in Jakarta.